2009
DOI: 10.1021/ma901535p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Photoinitiated Frontal Polymerization. Influence of UV Light Intensity Variations on the Conversion Profiles

Abstract: UV polymerizations in the presence of a photobleachable initiator are studied. The photoinitiator concentration vs time and the UV radiation intensity evolution within the sample are calculated according to rate equations. Polymerization and temperature profiles inside the sample are calculated assuming steady-state conditions. Thermal boundary conditions are chosen for orthopedic applications. The polymerization is then investigated under a range of photoinitiation conditions to access the ability to form thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…An ideal reaction of FPP should satisfy three factors, namely light absorption, photobleaching and restricted mass transfer . Many fundamental studies on kinetics have provided guidance for the construction of an FPP system . Recently, FPP has provided a means for the fabrication of functional materials for microfluidic applications and patterning .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal reaction of FPP should satisfy three factors, namely light absorption, photobleaching and restricted mass transfer . Many fundamental studies on kinetics have provided guidance for the construction of an FPP system . Recently, FPP has provided a means for the fabrication of functional materials for microfluidic applications and patterning .…”
Section: Introductionmentioning
confidence: 99%
“…21 Many fundamental studies on kinetics have provided guidance for the construction of an FPP system. [22][23][24][25] Recently, FPP has provided a means for the fabrication of functional materials for microfluidic applications and patterning. 26,27 However, limited work has been attempted to explore the preparation of hydrogels by FPP.…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have proposed some models to account for the frontal polymerization and it has been concluded that if the photoinitiator bleaches, the front propagates at a constant velocity in the sample . This has been used to generate gradient optical materials or microfluidic devices …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al employed two‐exponent expressions for the monomer conversion. Hayki et al analyzed frontal photopolymerization considering auto‐acceleration parameters . However, while there have been many measurements of the monomer conversion as a function of time, regional molecular‐weight distributions have not been theoretically analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Hayki et al analyzed frontal photopolymerization considering auto-acceleration parameters. [19] However, while there have been many measurements of the monomer conversion as a function of time, regional molecular-weight distributions have not been theoretically analyzed. While the number-averaged molecular weight as the spatially homogenous sample is determined by GPC analysis, etc., determination of practical cure depths requires local distribution of the molecular weight.…”
Section: Introductionmentioning
confidence: 99%